Compressive deformation behavior modeling of AZ31 magnesium alloy at elevated temperature considering the strain effect - Gh. A. Nourollahi; M. Farahani; A. Babakhani; S. S. Mirjavadi (Materials Research, 2013)
The true stress-strain data from isothermal hot compression tests, in the temperature range of 300-500 ºC and strain rate of 0.001-0.1s-1, were employed to study the flow behavior of AZ31 and to develop constitutive equation based on an Arrhenius-type equation. The flow stress increases with the decrease of deformation temperature and the increase of strain rate, which can be represented by Zener-Hollomon parameter in an exponential equation. The influence of strain was incorporated in the developed constitutive equation by considering the effect of strain on material constants. The results show that the proposed constitutive equations give a precise estimate for high temperature flow stress AZ31 alloy, which means it can be used for numerical simulation of hot deformation process and for choosing proper deformation parameter in engineering practice accurately.